The Role of Work Competence and Compensation on Increasing Organizational Commitment - Gienardy, Melda; Mulyaningsih Kamaru, Sri; Fitarini Sibay, Yusnita (Journal of Management, 2024)
Organizational commitment is an important component in employee retention and effectiveness. The purpose of this study is to look into how work competency and compensation affect organizational commitment in the workplace.This quantitative study used multiple regression analysis to investigate the links between work competency, remuneration, and organizational commitment. Data were gathered via structured questionnaires delivered to a sample of employees. The measurement instruments' validity and reliability were verified, and the data were analyzed with t-tests, ANOVA, and regression analysis. The study found that work competence has a significant positive effect on organizational commitment (t = 2,569, p = 0.012). In contrast, salary has no significant effect on organizational commitment (t = 1,095, p = 0.276). The regression model explains roughly 47.8% of the variance in organizational commitment, with an adjusted R Square of 46.8%, indicating that the model is reasonably effective at capturing the impact of job competence and compensation on organizational commitment. The study shows that work competence greatly leads to increased organizational commitment, although compensation has no significant effect in this regard. Organizations should prioritize improving their workers' work competency as a method for increasing organizational commitment. Further research is suggested to investigate additional elements impacting organizational commitment and validate these findings in various contexts.